Entrepreneurial Learning as a Mediator between Entrepreneurial Orientation and SME Performance: A Conceptual Model and Research Propositions - Abubakar, Ramatu Abdulkareem; Kurab, Kabiru Maitama (School of Social Sciences, USM, 2017)
Although a considerable amount of academic research has consistently established significant positive relationship between entrepreneurial orientation and small and medium enterprises’ performance, there remains a paucity of research examining the fundamental processes behind this relationship. To address this theoretical gap in the literature, a proposed mediation model is proposed. The proposed conceptual model and propositions developed was based on resource-based view (RBV) and relevant extant literature in the fields of marketing, strategic management, and entrepreneurship. In this paper, we provide a detail review of literature linking entrepreneurial orientation and SME performance. In addition, we review some extant literature to show why and in what ways entrepreneurial learning might play a mediating role between entrepreneurial orientation and SME performance. Managerial implications, limitations and further research are discussed.